Cutaneous protothecosis in a dog successfully treated with oral itraconazole in pulse dosing - Gmyterco, Vanessa Cunningham; Jagielski, Tomasz; Baldasso, Gustavo; Bacher, Louise Helene; Ribeiro, Márcio Garcia [UNESP]; de Farias, Marconi Rodrigues (Springer Nature, 2023)
Background: Protothecosis is a rare infectious disease caused by unicellular, achlorophyllous, microalgae of the genus Prototheca, ubiquitously distributed in nature. The algae are emerging pathogens, whose incidence is increasing in both human and animal populations and serious systemic infections related to this pathogen have been increasingly described in humans in recent years. After mastitis in dairy cows, canine protothecosis is the second most prevalent form of the protothecal disease in animals. Here, we report the first case of chronic cutaneous protothecosis due to P. wickerhamii in a dog in Brazil, successfully treated with a long-term therapy with itraconazole in pulse. Case presentation: Upon clinical examination, exudative nasolabial plaque, ulcered, and painful lesions in central and digital pads and lymphadenitis were observed in a 2-year-old mixed-breed dog, with a 4-month history of cutaneous lesions and contact with sewage water. Histopathological examination revealed intense inflammatory reaction, with numerous spherical to oval, encapsulated structures stained with Periodic Acid Schiff, compatible with Prototheca morphology. Tissue culture on Sabouraud agar revealed yeast-like, greyish-white colonies after 48 h of incubation. The isolate was subjected to mass spectrometry profiling and PCR-sequencing of the mitochondrial cytochrome b (CYTB) gene marker, leading to identification of the pathogen as P. wickerhamii. The dog was initially treated with oral itraconazole at a dosage of 10 mg/kg once daily. After six months, the lesions resolved completely, yet recurred shortly after cessation of therapy. The dog was then treated with terbinafine at a dose of 30 mg/kg, once daily for 3 months, with no success. The resolution of clinical signs, with no recurrence over a 36-months follow-up period, was achieved after 3 months of treatment with itraconazole (20 mg/kg) in pulse intermittently on two consecutive days a week. Conclusions: This report highlights the refractoriness of skin infections by Prototheca wickerhamii with therapies proposed in the literature and suggests a new treatment option with oral itraconazole in pulse dosing for long-term disease control successfully performed in a dog with skin lesions.
Keywords: CYTB gene; Genetic identification; MALDI-TOF MS; Prototheca sp; Prototheca wickerhamii